Income distribution, public services expenditures, and all cause mortality in US states. Issue 9 (12th August 2005) - Dunn, James R; Burgess, Bill; Ross, Nancy A
Abstract : Introduction: The objective of this paper is to investigate the relation between state and local government expenditures on public services and all cause mortality in 48 US states in 1987, and determine if the relation between income inequality and mortality is conditioned on levels of public services available in these jurisdictions. Methods: Per capita public expenditures and a needs adjusted index of public services were examined for their association with age and sex specific mortality rates. OLS regression models estimated the contribution of public services to mortality, controlling for median income and income inequality. Results: Total per capita expenditures on public services were significantly associated with all mortality measures, as were expenditures for primary and secondary education, higher education, and environment and housing. A hypothetical increase of $100 per capita spent on higher education, for example, was associated with 65.6 fewer deaths per 100 000 for working age men (p<0.01). The positive relation between income inequality and mortality was partly attenuated by controls for public services. Discussion: Public service expenditures by state and local governments (especially for education) are strongly related to all cause mortality. Only part of the relation between income inequality and mortality may be attributable to public service levels.